(untitled) (De Legibus - Revista de Direito da Universidade Lusófona Lisboa, 2022)
This essay is about some connections between the idea according to which free will and determinism are mutually compatible and the fundamentals of criminal imputation. It is sustained that the Principle of Alternative Possibilities remains indispensable as a starting point, without damage to its integration into a broader model, able to cover those situations where the moral agent intentionally (at least by negligence) produces (or do not avoid) the conditions of his own lack of liability in ordinary or general terms.